Factor VIII: the protein, cloning its gene, synthetic factor and now – 35 years later – gene therapy; what happened in between?. (3rd January 2020) - Ling, Gavin; Tuddenham, Edward G. D.
Summary: The foundation of haemophilia A therapy in the last 35 years has been critically dependent on isolation of the Factor VIII (FVIII) protein and discovery of the cDNA sequence of the FVIII gene, published in 1984. Identification of the FVIII sequence resulted in a new era of recombinant concentrates and led to significant improvements in safety, set against the tragedy of widespread HIV and hepatitis infections in haemophilia patients from contaminated plasma‐based products. We chronicle the scientific methods and race leading up to the publication of the FVIII DNA sequence and the legacy that follows through to revolutionary gene therapy treatment in clinical trials today.